PELATIHAN MENGGUNAKAN CD ANIMASI PEMBELAJARAN DAN MEMBUAT SOAL-SOAL INTERAKTIF SEBAGAI MEDIA SOSIALISASI CINTA ANAK TERHADAP PEMBELAJARAN MATEMATIKA DI TINGKAT TK DAN SD - Agung Handayanto; Puji Rahayu; Supandi IKIP PGRI Semarang; FM Dewanto; Rina DS (Universitas PGRI Semarang, 2011)
Abstract ?é?á Teaching mathematics for kindergarten and elementary students will be successful if the teaching learning process has a lot of interesting and exciting activities towards to students. Team of community service tries to give them the alternative method in order to make students more interested in joining the lesson. Using visual aids is the best way in transferring knowledge to understand mathematics easily. This training was given to the mathematics teachers of kindergarten and elementary in how to design some materials using animation and how to make interactive tests. The aim of this training was to equip the mathematics teachers to be able to use the CD animation and interactive tests related to their?é?á?é?á mathematic materials. The animation made was about playing and calculating by using PowerPoint Application 2007. By having this method, it is expected that mathematics teachers will be able to explore the lesson using it effectively and creatively. ?é?á Key words: mathematic, CD animation, interactive tests